Comparison between inclined treadmill sprint training and plyometric exercise in improving sprint performance among healthy young adults - Song, Jasmine Wen Hui (2022)
Improving sprint performance helps in allowing athletes that utilizes explosive sprint such as track and field, soccer, and basketball to have a greater advantage. Therefore, the effect of intervention that can improve sprint performance should be studied on. Besides, there are limited studies in comparing inclined treadmill sprint training and plyometric exercise among healthy young adults in sprint performance in Malaysia. The objective of the study is to compare inclined sprint training and plyometric exercise in improving sprint performance in improving sprint performance among healthy young adults. A quasi-experimental design will be used as the research design. The population will be done through quota sampling and will be screen using questionnaire. The participants will be randomly assigned to two groups. 10- meter dash, vertical jump test and standing long jump test are used to assess the sprint performance. Statistical analysis will be done using SSPS software and Microsoft excel. In the inclined treadmill sprint group, there is significant improvements in standing long jump test, vertical jump test and 10-meter dash (p0.05). There is no significant difference between inclined treadmill sprint and plyometric exercise in improving sprint performance among healthy young adults through analyzing the vertical jump test, peak power and 10-meter dash (p>0.05) while standing long jump (p <0.05) being the only outcome measure that is significant. This study concluded the effect of both inclined treadmill sprint and plyometric exercise are significant in improving sprint performance which are the standing long jump, vertical jump test and 10-meter dash over a period of 4 weeks. However, there is no significant difference found between both intervention group.